2018
DOI: 10.1088/1674-1056/27/3/034203
|View full text |Cite
|
Sign up to set email alerts
|

Implication of two-coupled tri-stable stochastic resonance in weak signal detection

Abstract: Stochastic resonance (SR) has been proved to be an effective approach to extract weak signals overwhelmed in noise. However, the detection effect of current SR models is still unsatisfactory. Here, a coupled tri-stable stochastic resonance (CTSSR) model is proposed to further increase the output signal-to-noise ratio (SNR) and improve the detection effect of SR. The effects of parameters a, b, c, and r in the proposed resonance system on the SNR are studied, by which we determine a set of parameters that is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Reference [17] proposed a novel adaptive stochastic resonance method based on coupled bistable systems, which compared with the cascaded bistable stochastic resonance system and suggested that coupled bistable SR system can enhance the target signal while suppressing the low-frequency and highfrequency interferences, whose output behavior exhibited good bandpass filtering characteristic. In Addition, multistable coupled systems have been researched continuously [18][19][20][21]. Based on the linear response theory, the output spectral amplification factor of the coupled system to the external periodic driving force is derived using the probability flow method, and the spectral amplification factor is further improved by adjusting the coupling coefficient and asymmetry factor.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [17] proposed a novel adaptive stochastic resonance method based on coupled bistable systems, which compared with the cascaded bistable stochastic resonance system and suggested that coupled bistable SR system can enhance the target signal while suppressing the low-frequency and highfrequency interferences, whose output behavior exhibited good bandpass filtering characteristic. In Addition, multistable coupled systems have been researched continuously [18][19][20][21]. Based on the linear response theory, the output spectral amplification factor of the coupled system to the external periodic driving force is derived using the probability flow method, and the spectral amplification factor is further improved by adjusting the coupling coefficient and asymmetry factor.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Subsequently, Xu et al have made some progress in the random non-smooth system. [23] Also, there are many researchers to obtain advances in SR. [24][25][26][27][28][29] In addition, the researchers also proposed many new SR models such as the Woods-Saxon model. [30][31][32] However, for most domestic and foreign research on SR, the classic bistable SR model based on four-time reflection symmetry potential is mostly studied.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The SR studies mainly focus on bistable stochastic resonance but also including monostable stochastic resonance [7][8][9] and tristable stochastic resonance. [10][11][12] The SR of this paper is referred to as the bistable stochastic resonance.…”
Section: Introductionmentioning
confidence: 99%